The association of plasma miR-155 and VCAM-1 levels with coronary collateral circulation. (February 2017) - Wang, Junnan; Yan, Youyou; Song, Dandan; Liu, Lulu; Liu, Bin
Aim: Inflammation plays an important role in development of coronary collateral circulation (CCC). The aim of this study is to determine whether the inflammation-related miRNA miR-155 and the inflammation marker VCAM-1 could be a biomarker for CCC.Patients & methods: We measured levels of plasma VCAM-1 and miR-155 in patients with CCC according to Rentrop grade by ELISA or real-time polymerase chain reaction, respectively (n = 112).Results: Plasma miR-155 was negatively correlated with VCAM-1 in the poor CCC group and with Rentrop grade in all patients with CCC. In addition, plasma VCAM-1 was significantly decreased in CAD patients with CCC.Conclusion: Plasma miR-155 might be a potent independent predictor of collateral formation.